A tin disulfide nanosheet wrapped with interconnected carbon nanotube networks for application of lithium sulfur batteries. (1st August 2019) - Jiang, Shouxin; Chen, Manfang; Wang, Xianyou; Zeng, Peng; Li, Yongfang; Liu, Hong; Li, Xiaolong; Huang, Cheng; Shu, Hongbo; Luo, Zhigao; Wu, Chun
Abstract: The shuttle effect of lithium polysulfides (LiPSs) seriously affects the cycle and rate capability performances of lithium sulfur batteries (LSBs) and restricts their commercial application. In order to suppress availably the shuttle effect of LiPSs, herein a holistic design strategy for using tin disulfide nanosheet wrapped with interconnected carbon nanotube networks (SnS2 @CNT) as the sulfur host and separator of LSBs is put forward. Based on the advantages of physical internment and chemistry absorption for LiPSs as well fast electron/lithium ion transport of SnS2 @CNT, the LSBs with SnS2 @CNT/S-SnS2 @CNT release a high initial discharge specific capacity of 1375 mAh g −1 at 0.1C. After 800 cycles a high reversible specific capacity of 555 mAh g −1 can still be obtained even at a high current density of 2C. Besides, the LSBs with the high sulfur loading of 4.8 mg cm −2 can exhibit a reversible areal capacity of 4.5 mAh cm −2 after 50 cycles. Therefore, the design strategy provides a beneficial exploration for the commercialization of high-performance LSBs. Graphical abstract: Image 103289 Highlights: A tin disulfide nanosheet wrapped with carbon nanotube network is prepared. The material is used as the sulfur host and modified separator. This strategy can effectively inhibit shuttle effect of polysulfides. The battery exhibits excellent electrochemical performance.